Recurrent pneumonia in malnourished children - Dewi, Putu Ria A.; Biantara, I Gede Yogi Priyatna; Windiyanto, Romy (International Journal of Research in Medical Sciences, 2022)
Recurrent pneumonia was defined as two episodes of pneumonia per year or three episodes of pneumonia at any time of life. The causes of recurrent pneumonia are multifactorial. Additional diagnostic should be considered because most cases are associated with an underlying illness. We reported a case recurrent pneumonia of a 3 months old malnourished male patient. Chest radiograph show infiltrate in both lung with history hospitalized for pneumonia one month before admission. Recurrent pneumonia occurs in 7.7-9% of children with community-acquired pneumonia. Several related conditions such as malnutrition, anatomic defect, immunodeficiency and other underlying illness can cause recurrent pneumonia.